Interactions of Liposomes and Platelets - Reinish, L W; Bally, M B; Loughrey, H C; Cullis, P R (Thrombosis and Haemostasis, 1988)
Rats were injected intravenously with liposomes of various compositions and sizes and blood platelet count measured. It was found that negatively-charged liposomal systems produced a transient reduction in platelet count in the first 5 minutes after injection which recovered by 60 minutes post-injection. This effect was most striking for multilamellar vesicles (MLV’s) containing phosphatidylglycerol (PG). Dose levels of 25 mg/kg of MLV’s containing 10 mole% PG caused the platelet count to drop from a control value of 1,086 ± 21 × 109/1 to 193 ± 14 × 109/1 by 2 minutes post-injection, an 82% decline. This thrombocytopenic effect was observed to diminish as vesicle size or vesicle dose was decreased. Positively-charged liposomes produced a less pronounced transient reduction in platelet count while neutral liposomes caused only a mild, transient platelet decline. This transient thrombocytopenic effect was not blocked by common anticoagulants and fibrinolytic agents but was pi evented by liposomal pretreatment. Radiolabeled platelet studies revealed that transient sequestration of platelets occurs in the liver and spleen 2 minutes after PG :EPC:CHOL MLV injection with a normalization of platelet distribution by 60 minutes post-injection. In vitro studies, using an automated blood counter suggest a transient association of liposomes and platelets occurring following injection. Liposomally-induced transient thrombocytopenia suggests a role for platelets in the biodistribution of liposomes.
Keywords: Liposomes; Platelets; Biodistribution; Transient thrombocytopenia